Laminated composite structure with embedded fibre optics - Hong, Kok Chian. (2008)
This is a final thesis of a Master's Research Project and it presents the investigation on the effect of the embedded optical fibres on the carbon fibre laminates using both experimental and numerical analysis. Experimental investigation includes the use of tensile test and the four-point jlexural test methods to study the influence of the optical fibre implants on the mechanical performance and properties of the carbon fibre laminates. Fibre Bragg Grating (FBG) Interrogating System is also used to measure the internal strain of the [0°]20 carbon fibre laminates as it undergoes 4-point flexural loading. Scanning electron microscopy (SEM) is also used to characterise the effect of the embedded optical fibre on the carbon fibre laminates with regard to the formation of voids or resin rich areas. The observations from the micrograph pictures showed optical fibre should be embedded between plies of 0° or parallel to the reinforcing fibres to prevent the bending of the plies and creation of voids and resin rich region which will lead to delamination under loading.